ANALISIS KOMPARATIF USAHATANI CABAI KERITING METODE PANEN MUDA DAN PANEN TUA DI KABUPATEN ROKAN HULU - Vaulina, Sisca (LPPM Universitas Malikussaleh - Indonesia, 2025)
Rokan Hulu Regency is a potential chili-producing area in Riau Province. This study aims to analyze (1) farmer characteristics, (2) cultivation technology, (3) costs, production, income, and efficiency, and (4) comparisons of costs, production, income, and efficiency in curly chili farming using early harvest and late harvest methods. The research used a survey method with purposive sampling, involving 15 green chili farmers and 25 red chili farmers. Data analysis was conducted using both qualitative and quantitative descriptive methods with SPSS. The results show that early-harvest chili farmers have an average age of 54, higher than late-harvest farmers (51 years). The education level of early-harvest farmers (high school) is higher than that of late-harvest farmers (junior high school). Early-harvest farmers have been farming longer (16 years) than late-harvest farmers (14 years). They also have more family dependents (3 people) than late-harvest farmers (2 people). The cultivation technology used aligns with farming theories. The total cost of early harvest curly chili farming is Rp 9,744,277/Ha/MT, with a production of 840.66 Kg/Ha/MT, a net income of Rp 11,272,390/Ha/MT, and an RCR of 2.07. Meanwhile, late harvest farming has a total cost of Rp 16,931,662/Ha/MT, a production of 1,904.4 Kg/Ha/MT, a net income of Rp 45,060,338/Ha/MT, and an RCR of 3.58. There is a significant difference in costs, production, income, and efficiency between early and late harvest curly chili farming in Ujung Batu District, Rokan Hulu Regency.